Non-Adherence To Childhood HPV Vaccination Is Associated With Non-Participation In Cervical Cancer Screening – A Nationwide Danish Register-Based Cohort Study - Badre-Esfahani S; Larsen MB; Seibæk L; Petersen LK; Blaakær J; Støvring H; Andersen B (Clinical Epidemiology, 2019)
Sara Badre-Esfahani,1,2 Mette Bach Larsen,1 Lene Seibæk,2 Lone Kjeld Petersen,3 Jan Blaakær,3 Henrik Støvring,4 Berit Andersen1 1Department of Clinical Medicine, Aarhus University, Aarhus C DK-8000, Denmark; 2Department of Gynaecology and Obstetrics, Aarhus University Hospital, Aarhus N DK-8200, Denmark; 3Department of Gynaecology and Obstetrics, Odense University Hospital, Odense C DK-5000, Denmark; 4Department of Public Health, Aarhus University, Aarhus C DK-8000, DenmarkCorrespondence: Sara Badre-EsfahaniDepartment of Public Health Programmes, Randers Regional Hospital, Skovlyvej 15, Randers DK-8930, DenmarkTel +45 8 78 42 01 72Fax +45 8 78 42 43 45Email sarbad@rm.dkBackground: The combination of organized cervical cancer screening and childhood HPV vaccination programs has the potential to eliminate cervical cancer in the future. However, only women participating in both programs gain the full protection, and combined non-attenders remain at high risk of developing cervical cancer. Our aim was to analyze the association between non-adherence to HPV vaccination and non-participation in cervical cancer screening for the total population and stratified by native background and parental education.Participants: Women born in 1993 eligible for both childhood HPV vaccination and first cervical cancer screening.Analysis: Logistic regression models were used to estimate the odds ratio (OR) of non-participation in cervical cancer screening with 95% confidence intervals (CI). Stratified and adjusted logistic regression models were used along with the Wald test in order to test for interaction.Results: 24,828 women were included in the study. Among vaccinated women, 61.4% participated in cervical cancer screening; only 39.0% of unvaccinated women participated in cervical cancer screening. Unvaccinated and unscreened women were often non-native and had the lowest socio-economic status, whereas vaccinated and screened women were often native and had the highest socio-economic status. The adjusted OR for non-participation in cervical cancer screening was 2.07 [95% CI: 1.88–2.28] for unvaccinated compared to vaccinated women. After stratifying by country of origin, unvaccinated natives had the highest adjusted OR of not participating in cervical cancer screening compared to non-native women from both western and non-western countries (adjusted ORs of 2.2 [95% CI: 2.0–2.4], 1.3 [95% CI: 0.6–2.8], and 1.5 [95% CI: 1.1–2.0], respectively) (Wald test p=0.019).Conclusion: Among natives, non-adherence to HPV vaccination and non-participation in screening seem to be signs of generally poor health-preventive behavior, whereas among non-natives from non-western countries, non-attendance in HPV vaccination and cervical cancer screening seem to be influenced by unrelated factors. Therefore, a differentiated and culturally sensitive approach is needed to enhance overall cervical cancer preventive behavior across different nativities.Keywords: human papilloma virus, vaccination, screening, non-participation, socio-economic status, nationality